Driving forces behind the management of Institutional Repositories: Qualitative evidences - Adam, Usman Ahmed; K., Kiran (Malaysian Journal of Library and Information Science, 2021)
An Institutional repository (IR) is a contemporary paradigm of scholarly communication that operates on a open access initiative. IRs have become essential infrastructure for the global research community with the expectation that IRs will address the issues of visibility, and facilitate the rapid dissemination of knowledge in a sustainable manner. However, scholars show concern about these expectations due to some shortcomings in the management of repositories and digitization projects, especially in Africa. This study aims to gain a deeper understanding of how personnel involved in institutional repository at their respective institutions are managing the IR, and identify the driving forces behind the management of these IRs. It also attempts to explore the key challenges in the context of IR management, specifically in Nigeria. The study adopts a descriptive qualitative approach using a semi-structured interview guide as the main instrument for data collection, supported by content analysis and group discussions. Three research questions were constructed to guide the investigation: (a) How are IRs being managed in Nigeria? (b) What are the driving forces behind the management of IRs in Nigeria? An (c) What are the challenges in the management of IRs in Nigeria? Findings reveal that manager of IRs are heavily dependent on mediated depositing and digitization processes. Increasing visibility and ranking of the institution, need for preservation, and need for organization of intellectual output, were among the key drivers of IR management. While, plagiarism, piracy, absence of guiding policies, and inadequate internet connectivity were among the hinderances faced in the management of IRs. The results are imperatively useful for practitioners, especially those managing or aspiring to manage successful IRs in developing countries, particularly in Africa. The study recommends strategic development and enforcement of policies by the institutions, use of similarity checkers, massive awareness creation and staff training for the success of IR management in Nigeria.